2020
DOI: 10.3324/haematol.2020.253781
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of ruxolitinib as a front-line therapy for 12 children with secondary hemophagocytic lymphohistiocytosis

Abstract: Hemophagocytic lymphohistiocytosis (HLH) is an immune-regulatory disorder characterized by excessive production of inflammatory cytokines. The treatment recommendations of the HLH-1994 and HLH-2004 protocols have long been used in HLH therapy, but some patients still do not respond well to or have unacceptable side effects from conventional therapies. It is believed that cytokine-targeted strategies that directly target disease-driving pathways will be promising options for HLH. This prospective study aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Eight out of 12 patients (66.7%) achieved complete response by day 28. With a median follow‐up of 8.2 months, five of 12 patients had an event, leading to an estimated 6‐month event‐free survival of 58.3% 65 . Finally, Meyer and coauthors showed that ruxolitinib treatment sensitizes CD8+ T cells to dexamethasone‐induced apoptosis 66 ; they found that IL‐2 and IL‐12 induce resistance to dexamethasone in this cell subset, via STAT5, by altering cellular apoptotic potential and that this can be reverted by the administration of ruxolitinib.…”
Section: Ifn‐γ In Hlhmentioning
confidence: 99%
“…Eight out of 12 patients (66.7%) achieved complete response by day 28. With a median follow‐up of 8.2 months, five of 12 patients had an event, leading to an estimated 6‐month event‐free survival of 58.3% 65 . Finally, Meyer and coauthors showed that ruxolitinib treatment sensitizes CD8+ T cells to dexamethasone‐induced apoptosis 66 ; they found that IL‐2 and IL‐12 induce resistance to dexamethasone in this cell subset, via STAT5, by altering cellular apoptotic potential and that this can be reverted by the administration of ruxolitinib.…”
Section: Ifn‐γ In Hlhmentioning
confidence: 99%
“…Indeed, a pilot study in 12 children with secondary HLH showed a good clinical response after 28 days of oral treatment. 90 Partial response was also reported for two Still’s patients with the concurrent use of steroids. 85 …”
Section: Novel Biologics Treatmentsmentioning
confidence: 81%
“…Since they were concomitantly affecting different proinflammatory pathways, these drugs could simultaneously target IFN-γ and other pathogenic mechanisms of MAS during AOSD, possibly allowing for better management of cytokine storm syndrome in these patients [ 61 ]. On these bases, recent evidence has shown ruxolitinib may be considered for patients with secondary HLH with contraindications to glucocorticoids, with a good clinical response [ 62 , 63 , 64 ].…”
Section: Discussion and Appraisal Of Literaturementioning
confidence: 99%